2014
DOI: 10.1177/0095798414563748
|View full text |Cite
|
Sign up to set email alerts
|

Hope as a Moderator of the Relationship Between Interpersonal Predictors of Suicide and Suicidal Thinking in African Americans

Abstract: Suicide is currently the third leading cause of death of African Americans between the ages of 15 and 24 years. Possible risk factors of suicidal ideation for this population include the two interpersonal constructs of the Interpersonal Theory of Suicide, perceived burdensomeness and thwarted belongingness. Past research has demonstrated that hope is negatively associated with each of these two constructs of the Interpersonal Theory of Suicide and suicidal ideation. The aim of the current study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
4
33
1
Order By: Relevance
“…The third hypothesis, that pathways would weaken the association between relationship status and thwarted belongingness, was also not supported. These results are inconsistent with previous studies that indicate agency and pathways reduce the likelihood of thwarted belongingness and suicidal behavior (Anestis et al., ; Davidson et al., ; Hollingsworth et al., ; Wai et al., ). The current findings suggest that for gay men, agency is not likely to be protective in weakening the association between relationship status and thwarted belongingness, nor the association between thwarted belongingness and suicidal behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The third hypothesis, that pathways would weaken the association between relationship status and thwarted belongingness, was also not supported. These results are inconsistent with previous studies that indicate agency and pathways reduce the likelihood of thwarted belongingness and suicidal behavior (Anestis et al., ; Davidson et al., ; Hollingsworth et al., ; Wai et al., ). The current findings suggest that for gay men, agency is not likely to be protective in weakening the association between relationship status and thwarted belongingness, nor the association between thwarted belongingness and suicidal behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have demonstrated associations between high levels of hope and low levels of thwarted belongingness (Anestis, Moberg, & Arnau, ; Davidson, Wingate, Slish, & Rasmussen, ) and between high levels of hope and low levels of suicidal ideation (O'Keefe & Wingate, ; Tucker et al., ). Furthermore, Hollingsworth, Wingate, Tucker, O'Keefe, and Cole () found in African American adults that hope moderated the relationship between thwarted belongingness and suicidal ideation, while controlling for depressive symptoms. Hollingworth et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Hope is a potential therapeutic target for intervention to improve mental health outcomes in young adults attending college. Hope is a protective factor in suicide risk 13,17,18 and is associated with positive health practices such as less alcohol use, less binge drinking, less smoking, more frequent exercising, and more dietary fat limitation 19 among college students. Also, hope is associated with positive mental well-being 3,4,20,21 a higher-Grade Point Average (GPA), 20,22,23 better school engagement, 20 a higher likelihood of graduating, and a lower likelihood of dismissal.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research indicates that developing a sense of hope can decrease the negative effects of rumination and suicidal ideation (Tucker et al, ). Research with African American (Hollingsworth, Wingate, Tucker, O'Keefe, & Cole, ) and Hungarian (Chang et al, ) college students supports this counteraction. An early retiree program (Lapierre, Dubé, Bouffard, & Alain, ) focused on building hope through goal setting resulted in decreased suicidal ideation and depression and was found to be effective.…”
Section: Shores: a Supported Mnemonicmentioning
confidence: 99%